2019
DOI: 10.3390/jcm8111763
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of c-Jun NH2-Terminal Kinase for Islet Transplantation

Abstract: Islet transplantation has been demonstrated to provide superior glycemic control with reduced glucose lability and hypoglycemic events compared with standard insulin therapy. However, the insulin independence rate after islet transplantation from one donor pancreas has remained low. The low frequency of islet grafting is dependent on poor islet recovery from donors and early islet loss during the first hours following grafting. The reduction in islet mass during pancreas preservation, islet isolation, and isle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…The p38MAPK pathway responds and adapts to numerous extracellular stimuli through downstream targets, which include protein kinases, phosphatases, transcription factors, and cell-cycle regulators. It has come to light that c-Jun participates in the JNK and stress-activated MAPK signaling pathways [ 50 ]. MK5, which is directly phosphorylated by MAPK4/6 (Erk3/4), could be phosphorylated and catalyzed by p38 MAP kinase instead of JNK [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The p38MAPK pathway responds and adapts to numerous extracellular stimuli through downstream targets, which include protein kinases, phosphatases, transcription factors, and cell-cycle regulators. It has come to light that c-Jun participates in the JNK and stress-activated MAPK signaling pathways [ 50 ]. MK5, which is directly phosphorylated by MAPK4/6 (Erk3/4), could be phosphorylated and catalyzed by p38 MAP kinase instead of JNK [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The p38MAPK pathway responds and adapts to numerous extracellular stimuli through downstream targets, which include protein kinases, phosphatases, transcription factors, and cell-cycle regulators. It has come to light that c-Jun participates in the JNK and stress-activated MAPK signaling pathways [49]. MK5, which is directly phosphorylated by MAPK4/6 (Erk3/4), could be phosphorylated and catalyzed by p38 MAP kinase instead of JNK [50].…”
Section: Discussionmentioning
confidence: 99%
“…Although most pancreatic islet transplants use organs from heart-beating brain-dead (BD) donors, acute physiological changes after brain death of BD donors may still cause significant damage to islets from inflammatory events. Brain death can stimulate various cells to produce pro-inflammatory cytokines, and produce a so-called “cytokine storm”, including IL-1β in BD donors, which greatly reduces the islet yield, functionality, vitality, and engraftment after transplantation ( 8 ). One study has shown that the administration of exendin-4 to BD donors can reduce the expression of IL-1β, thereby increasing both the islet viability and insulin secretion in the pancreas after glucose stimulation in a BD rat model ( 81 ).…”
Section: Il-1βmentioning
confidence: 99%
“…It was observed that only 10% of recipients remain insulin dependent for more than 5 years and that most recipients re-use insulin because of a decline in the islet function over time ( 7 ). During transplantation, islet grafts are damaged by multiple challenges, including enzyme and mechanical damage caused by the isolation process, hypoxia, inflammation, immune rejection and toxicity of immunosuppressive drugs ( 8 ). The liver is currently the preferred transplantation site because the procedure is minimally invasive, easy to perform, and has low rates of bleeding and thrombosis ( 9 ).…”
Section: Introductionmentioning
confidence: 99%